Agile Scrum as a Development Approach: A Case Study of Web-based School Information System Design - Wandri, Rizky; Fadhilah, M Rizki; Setiawan, Panji Rachmat; Fadhilla, Mutia (Sistemasi: Jurnal Sistem Informasi, 2025)
The growing utilization of information technology presents substantial opportunity to enhance efficiency in school administrative activities. Nevertheless, numerous educational institutions continue to employ semi-manual processes with software like Microsoft Word and Excel, thereby significantly heightening the danger of human error. This research employs an Agile development strategy utilizing the Scrum framework to create a web-based school information system that is more efficient and responsive to user requirements. The evaluation results indicate that this system has effectively enhanced administrative efficiency and attained a user satisfaction rate of 95%, demonstrating the successful implementation of the Agile Scrum methodology in the educational setting. This system is anticipated to provide as an efficient solution for the integrated management of student, teacher, staff, and school financial data.